Long COVID in the context of social determinants of health - Lukkahatai, Nada; Rodney, Tamar; Ling, Catherine; Daniel, Brittany; Han, Hae-Ra (Frontiers in Public Health, 2023)
The COVID-19 pandemic has been a challenge for the public health system and has highlighted health disparities. COVID-19 vaccines have effectively protected against infection and severe disease, but some patients continue to suffer from symptoms after their condition is resolved. These post-acute sequelae, or long COVID, continues to disproportionately affect some patients based on their social determinants of health (SDOH). This paper uses the World Health Organization's (WHO) SDOH conceptual framework to explore how SDOH influences long COVID outcomes.